11'-α-Tocomonoenol is the major α-tocomonoenol isomer in cyanobacteria and microalgae from Costa Rica - Montoya Arroyo, Alexander (2022)
α-Tocomonoenols are vitamin E-derivatives with a single double-bond in the tocochromanol sidechain. Currently, two congeners are known: 11′-α-tocomonoenol and 12′-α-tocomonoenol, the later better known as “marine-derived tocopherol” (MDT). Information regarding their presence in photosynthetic aquatic organisms is scarce. We thus determined vitamin E congeners and derivatives in microalgae and cyanobacteria to assess their potential as sources of α-tocomonoenols. Tocochromanols were extracted from freeze-dried cyanobacteria (Arthrospira platensis) and microalgae (Nannochloropsis oceanica, Chlorella vulgaris and Tetraselmis sp.) and quantified by HPLC-FLD. α-Tocomonoenol was quantified in N. oceanica and Tetraselmis sp. where it was the second most abundant tocochromanol following α-tocopherol. LC-MSn and GC-MS confirmed that 11′-α-tocomonoenol and not MDT was the predominant α-tocomonoenol form in evaluated cyanobacteria and microalgae. No significant correlations were observed between tocomonoenol or vitamin E contents and fatty acid profiles. In conclusion, microalgae and particularly Tetraselmis sp. are novel sources of 11′-α-tocomonoenol, a tocochromanol not previously reported in aquatic photosynthetic organisms.